The Impact of Influencer Marketing on Brand Image, Brand Awareness, and Brand Trust toward Purchase Decisions for Skincare Products - Diandra Gratia Sumanti; Paulus Kindangen; Ferdinand J. Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Influencers are changing the way brands interact with the public, consumers, and other brands, it is a new phenomenon that is having a major impact on everyone’s lifestyle. In view of this situation, it is very important for a brand to have an in-depth understanding of how significant the impact of influencer marketing is on brand development, causing consumers to buy a skincare product. This research mainly explores the impact of influencer marketing on purchasing decisions for skincare products through brand image, brand awareness, and brand trust in Generation Z at the Faculty of Economics and Business, Sam Ratulangi University. This study has used a quantitative approach with SEM-PLS as method analysis, the sampling technique used cluster sampling with the number of samples obtained as many as 100  respondents. The analysis technique used in this study is the path analysis method. The results find that influencer marketing through TikTok positively impacted brand image, awareness, and trust. Brand image and brand awareness positively impact purchase decisions for skincare products while brand trust negatively impacts purchase decisions for skincare products. Brand image, brand awareness, and brand trust also significantly mediate the impact of influencer marketing on purchase decisions.   Keywords: Influencer Marketing, Brand Image, Brand Awareness, Brand Trust, Purchase Decisions